Fabrication and characterization of InGaAs/InAIAs semiconductor structures Lattice Matched on (100) InP grown via Molecular Beam Epitaxy - Misa, John Vincent
InGaAs, InAlAs and InAlAs/InGaAs/InAlAs semiconductor structures lattice matched to Indium Phosphide were grown using Molecular Beam Epitaxy in order to extend the operation of semiconductor optoelectronic devices to the 1.3 and 1.5 micrometer regions which are coincident with low loss and low dispersion in silica based optical fibers for applications in telecommunication. The In0.53Ga0.47As Pn junction lattice matched on lnP was grown at 490ᵒC substrate temperature, In/Ga flux ratio of 1.53 and 4.0x10-5 Torr As flux. Gorwth of In0.53Ga0.47As on InP was accomplished at 500ᵒC growth temperature at an In/Al flux ratio of 2.83 under a 2.4x10-5 Torr as flux. The lattice matched in In0.64Al0.36As/ In0.53Ga0.47As/ In0.64Al0.36As PIN heterostructure was grown at 510ᵒC for InAlAs layers and 500ᵒC for InGaAs under an As flux of 2.4x10-5 Torr. In/Ga and In/Al flux ratios of 1.13 and 2.02 respectively were maintained for each corresponding layer grown. Scanning Electron Microscopy shows anisotropy in growth as manifested by the differences in cross section features as well as the growth of islands lying along the 011 direction. Photocurrent measurements done on fabricated 250 micrometer mesa devices reveal peak response at 0.92 and 1.25 micrometers for InAlAs and InGaAs respectively. The 250 micrometer heterostructure device exhibits peaks at 1.26 and 1.43 micrometers which are well within the desired operating ranges.